P11.31 EB1-dependent survival of glioblastoma tumor-bearing mice after treatment with the novel checkpoint activator BAL101553 is associated with inhibition of cancer stem-like cell-mediated tumor angiogenesis and astrocytic differentiation. (6th September 2019) - Berges, R; Tchoghandjian, A; Serge, A; Honore, S; Figarella-Branger, D; Bachmann, F; Lane, H; Braguer, D
Abstract: BACKGROUND: Glioblastoma (GBM) patients have limited treatment options. Cancer stem-like cells (CSLCs) contribute to GBM invasiveness, representing promising targets. BAL101553 is a novel small molecule tubulin-binding agent, promoting tumor cell death through spindle assembly checkpoint activation, which is currently in Phase 1/2a in advanced solid tumor patients including GBM. We have shown that overexpression of microtubule + end-binding 1-protein (EB1) correlates with GBM progression and poor survival. This study aimed to evaluate the effect of short-term IV and long-term daily oral BAL101553 treatment on mice orthotopically grafted with GBM CSLCs (GBM6) according to EB1 expression-level, and to decipher its mechanism of action on CSLCs. MATERIAL AND METHODS: The A2B5+ GBM6 cell line was established from CSLCs isolated from a GBM patient. GBM6 cells display a mesenchymal phenotype with a high tumorigenicity and infiltrative pattern of migration. As EB1 is overexpressed in GBM6, we investigated drug activity on GBM6 according to EB1 expression, by using EB1-expressing cells (GBM6-GFP-sh0) and EB1-downregulated (GBM-GFP-shEB1) cells. BAL27862 is the active moiety of the prodrug BAL101553, which was developed to improve solubility. Two sets of animal experiments were performed with 4 groups randomized for GBM6-GFP-sh0- and GBM6-GFP-shEB1-bearing mice, receiving either BAL101553 (25 mg/kg) or vehicle intravenously on day 30, 33, and 36 after glioma implantation, or BAL101553 (30 mg/kg) or vehicle orally from day 35–135 post-grafting (5 days dosing/week). Survival and tumor invasion were analyzed. In vitro, BAL27862 activity was tested by using a cytotoxicity assay, and endothelial cell capillary-like tube formation assay. RESULTS: Both treatment schedules provided an EB1-expression level-dependent survival benefit; with daily oral treatment this was almost one year longer than observed in vehicle-treated mice. Moreover, the anti-proliferative and anti-invasive effects of BAL101553 were more potent in mice bearing EB1-expressing tumors as compared to EB1-downregulated tumors. This was associated with inhibition of stem cell properties. Formation of vascular structures by the fluorescent GBM6-GFP-sh0 cells was observed in the brains of grafted mice. Drug treatment counteracted the formation of brain tumor vessels by inhibiting GBM6 trans-differentiation into tumor-derived endothelial cells, as well as VEGF secretion; thus, preventing normal endothelial cell migration activated by CSLCs. CONCLUSION: BAL101553/BAL27862 triggers astrocytic differentiation and counteracts tumor angiogenesis by acting on CSLCs; thus, potentially adding to the direct anti-tumor cell effect. A high level of EB1 expression in CSLCs potentiates the drug's effects, suggesting the potential of EB1 expression as a response-predictive biomarker for BAL101553 in GBM.